2008
DOI: 10.1038/bjp.2008.368
|View full text |Cite
|
Sign up to set email alerts
|

Benzylidene derivatives of andrographolide inhibit growth of breast and colon cancer cells in vitro by inducing G1 arrest and apoptosis

Abstract: Background and purpose: Andrographolide, the major phytoconstituent of Andrographis paniculata, was previously shown by us to have activity against breast cancer. This led to synthesis of new andrographolide analogues to find compounds with better activity than the parent compound. Selected benzylidene derivatives were investigated for their mechanisms of action by studying their effects on the cell cycle progression and cell death. Experimental approach: Microculture tetrazolium, 3-(4,5-dimethylthiazol-2-yl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…1) exhibit an enhanced ability to induce apoptosis and G1 cell-cycle arrest in breast and colon cancer cells (25,27). Other studies have shown that AGP interferes with MAPK activation, increases sensitivity of Ras-transformed cells to radiation treatment in vitro and in vivo (27)(28)(29)(30), and is not toxic (31).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) exhibit an enhanced ability to induce apoptosis and G1 cell-cycle arrest in breast and colon cancer cells (25,27). Other studies have shown that AGP interferes with MAPK activation, increases sensitivity of Ras-transformed cells to radiation treatment in vitro and in vivo (27)(28)(29)(30), and is not toxic (31).…”
Section: Resultsmentioning
confidence: 99%
“…5F). Moreover, the ability of AGP, SRJ09, and SRJ23 to induce growth inhibition against PC-3 (prostate), HCT-116 (colon), and MDA-231 (breast) cancer cells was assessed as described previously (25). PC-3 cancer cells harbor wild-type Ras for all of the three different isoforms (H-, K-, and N-Ras), whereas HCT-116 and MDA-231 cancer cells express G13D mutant K-Ras and wild-type H-and N-Ras.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrographolide protected normal cells against chemical induced toxicity (Ye et al, 2011). Andrographolide induced G0/G1 cell cycle arrest in various types of cancer cells (Jada et al, 2008). The cytotoxic activity of andrographolide is probably due to intact U-butyrolactone ring, the double bonds between C-12 and C-13, C-8 and C-17 and hydroxyl group at C-14 present in the chemical structure of andrographolide (Varma et al, 2009;Sirion et al, 2012).…”
Section: Discussionmentioning
confidence: 99%